The Incidence And Different Risk Factors For The Recurrence Of Chronic Subdural Hematoma: A Retrospective Study (Journal of Pharmaceutical Negative Results, 2022)
Background and Aim: Chronic subdural hematoma is a neurosurgical condition that represents degradation of liquefied blood collected abnormally beneath the dura that typically forms within three weeks. The recurrent rates of chronic subdural hematoma after surgery varies from 5% to 30%. However, different risk factors that lead to recurrent chronic subdural hematoma remain debatable. Therefore, the present study aimed to determine the incidence and different risk factors for recurrent chronic subdural hematoma.Methodology: A retrospective study was conducted on 206 chronic subdural hematoma patients admitted to the Department of Neurosurgery, Lady Reading Hospital, Peshawar Pakistan for the duration from 1st July 2020 to 30th June 2022. Prior to study conduction, ethical approval was taken from the institute ethical committee. Demographic details, trauma history, surgical intervention types, antithrombotic therapy, surgical drain usage, preoperative symptoms, postoperative symptoms, and clinical outcomes were retrieved from the medical record. SPSS version 25 was used for data analysis. Results: Out of 206 chronic subdural hematoma patients, there were 164 (79.6%) males and 42 (20.4%) females. The overall mean age was 62.9±16.2 years. The prevalence of recurrent chronic subdural hematoma was 28 (13.6%). The incidence of previous head trauma was found in 138 (67%) patients. The prevalence of left-side, right-side, and bilateral hematoma was 82 (39.8%), 58 (28.2%), and 66 (32%) respectively. In terms of hematoma density, the incidence of homogeneous hypo-dense, homogenous iso-dense, homogeneous hyperdense type, laminar type, separated type, and trabecular type were seen in 40 (19.4%), 46 (22.3%), 16 (7.8%), 10 (4.9%), 36 (17.4%), and 58 (28.2%) respectively. The overall mean of drainage time after initial intervention was 1.6± 0.8 days. All the patients underwent successful chronic subdural hematoma surgery.Conclusion: The present study found that the prevalence of recurrent chronic subdural hematoma was 13.6%. Male patients are more susceptible to chronic subdural hematoma recurrence compared to female patients. Post-surgery subdural drainage duration and homogeneous hyper-dense hematoma were the independent prognosticator of recurrent chronic subdural hematoma. The risk of recurrence was lower in cases where postoperative drainage of the subdural had longer duration.